Long‐chain polyunsaturated fatty acid supplementation in the first year of life affects brain function, structure, and metabolism at age nine years. Issue 1 (11th October 2018) - Lepping, Rebecca J.; Honea, Robyn A.; Martin, Laura E.; Liao, Ke; Choi, In‐Young; Lee, Phil; Papa, Vlad B.; Brooks, William M.; Shaddy, D. Jill; Carlson, Susan E.; Colombo, John; Gustafson, Kathleen M.
Abstract: The present study sought to determine whether supplementation of long‐chain polyunsaturated fatty acids (LCPUFA) during the first year of life influenced brain function, structure, and metabolism at 9 years of age. Newborns were randomly assigned to consume formula containing either no LCPUFA (control) or formula with 0.64% of total fatty acids as arachidonic acid (ARA; 20:4n6) and variable amounts of docosahexaenoic acid (DHA; 22:6n3) (0.32%, 0.64%, or 0.96% of total fatty acids) from birth to 12 months. At age 9 years (±0.6), 42 children enrolled in a follow‐up multimodal magnetic resonance imaging (MRI) study including functional (fMRI, Flanker task), resting state (rsMRI), anatomic, and proton magnetic resonance spectroscopy ( 1 H MRS). fMRI analysis using the Flanker task found that trials requiring greater inhibition elicited greater brain activation in LCPUFA‐supplemented children in anterior cingulate cortex (ACC) and parietal regions. rsMRI analysis showed that children in the 0.64% group exhibited greater connectivity between prefrontal and parietal regions compared to all other groups. In addition, voxel‐based analysis (VBM) revealed that the 0.32% and 0.64% groups had greater white matter volume in ACC and parietal regions compared to controls and the 0.96% group. Finally, 1 H MRS data analysis identified that N‐acetylaspartate (NAA) and myo ‐inositol (mI) were higher in LCPUFA groups compared to the control group. LCPUFA supplementation during infancy has lasting effects on brain structure, function, and neurochemical concentrations in regions associated with attention (parietal) and inhibition (ACC), as well as neurochemicals associated with neuronal integrity (NAA) and brain cell signaling (mI).